Interpreting interior heritage at Wisma Batari Surakarta through papanek’s framework - Prasetyo, Raden Ersnathan Budi; Mumpuni, Primastiti Wening; Budiwiyanto, Joko; Aji, Tunjung Bayu (Universitas Indraprasta PGRI, 2025)
This study analyzes the interior of Wisma Batari in Surakarta as a social design product by applying Victor Papanek’s function complex framework. Interior is not merely an architectural space, but a design artefact that embeds functions, needs, social contexts, symbols, and aesthetic values. The study employs a qualitative descriptive-interpretative method using visual observation and spatial analysis, complemented by thematic reading based on Papanek’s six dimensions: method, use, need, telesis, association, and aesthetics. The findings suggest that the interior of Wisma Batari forms a design system rooted in spatial efficiency, local materials as a reflection of “truth to materials,” and room configurations that support communal activity. Space is never practical alone; it also represents morality, harmony, and unity within Javanese cultural logic. The study highlights that interior heritage can be understood as a social design product that evolves through adaptive reuse and the interrelation of functions, meanings, and materiality. The implication of this research opens a critical approach toward interior heritage as a locus for ethics and social responsibility within contemporary design practices.